'Breaking the silence around menstruation': experiences of adolescent girls in an urban setting in India. Issue 2 (4th May 2017) - Rajagopal, Shobhita; Mathur, Kanchan
ABSTRACT: The onset of menstruation is one of the important changes that occur in the lives of adolescent girls. It brings many challenges with it. Menstruation is often dealt with in secrecy in many cultures and communities. In India, restrictions are placed on women and girls during menstruation, and the tradition of excluding menstruating women and girls from various activities continues. Adolescent girls also suffer from myriad health problems associated with menstruation. Many lack the facilities and resources they need for menstrual hygiene. This article draws on research into the experiences and challenges faced by adolescent girls in managing menstruation at school and home in the slums of Jaipur, Rajasthan. The article analyses the role and impact of government-led policy and interventions. It argues that the continued silence around menstruation needs to be broken: not only by addressing the practical issues of menstrual management, but also by creating a supportive environment for empowering girls with information about their bodies, and destigmatising the issue of menstruation. The article also draws lessons for policy advocacy.